Realist Evaluation - and Pawson, Ray; Tilley, Nick (2004)
Contents: Introduction 1. The nature of programmes and how they work 2. Basic concepts in the explanation and understanding of programmes 3. Strategies and methods of realist evaluation 4. Realism’s place in the policy cycle: formative, summative and synthetic approaches 5. The nature, presentation and use of findings from realist evaluation 6. Conclusion: strengths, limitations and relationships with other approaches Appendix I – ‘Thinking it through’: an exercise in realist hypothesis making. Appendix II – ‘Varieties of realist evaluation’: pocket illustrations of quantitative, qualitative, formative and synthetic applications. Appendix III – ‘Would it work here?’: a grid to help decide on the feasibility of mounting a programme ‘on your patch’.